2015
DOI: 10.1007/s10815-015-0428-z
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation and in-vitro fertilization outcomes of cancer patients undergoing fertility preservation compared to age matched controls: a 17-year experience

Abstract: Purpose To compare the in-vitro fertilization (IVF) outcomes of cancer patients who underwent oocyte retrieval and embryo/ oocyte cryopreservation prior to gonadotoxic therapy to those of age and time-matched controls with tubal factor infertility. Methods All cancer patients who underwent embryo/oocyte cryopreservation at our institution from 1997 to 2014 were reviewed. Primary outcomes were total dose of gonadotropins used, number of oocytes retrieved, and number of 2pn embryos obtained. Outcomes were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 40 publications
8
56
0
7
Order By: Relevance
“…Very recently, Cardozo et al also published their data on IVF outcomes of cancer patients undergoing fertility preservation, covering exactly the same 17-year period (1997-2014) as in our study [11]. They obtained a relative high utilization rate, as 21/63 (33 %) patients returned for frozen embryo transfer.…”
Section: Utilization Ratesupporting
confidence: 61%
See 2 more Smart Citations
“…Very recently, Cardozo et al also published their data on IVF outcomes of cancer patients undergoing fertility preservation, covering exactly the same 17-year period (1997-2014) as in our study [11]. They obtained a relative high utilization rate, as 21/63 (33 %) patients returned for frozen embryo transfer.…”
Section: Utilization Ratesupporting
confidence: 61%
“…However, their study published in 2015 on a series of 57 cancer patients who had embryos cryopreserved, showed a similar LBR per transfer between cancer patients and controls [11]. Hence, even if several other studies have reported lower numbers of retrieved oocytes compared to controls [5,7,19,20], this does not appear to have any impact on the pregnancy rate once the patient is cured [11,21].…”
Section: Pregnancy Ratementioning
confidence: 92%
See 1 more Smart Citation
“…There are scant reports based on small series which present reassuring live born rates in cancer patients who have returned for thawed embryo transfer [18][19][20][21]. The largest series, which include 21 cancer patients, display that pregnancy and live born rates achieved per transfer of thawed embryos, do not differ between fertility preservation patients and infertile (tubal/male factor) patients [22].…”
Section: Ovarian Response In Coh Cyclesmentioning
confidence: 99%
“…8 The technique has good yield for cancer survivors: in many studies, the number of oocytes frozen following stimulation is equivalent for cancer survivors and age-matched infertile controls without cancer. [43][44][45] Oocyte retrieval rates vary according to diagnosis, with higher retrieval rates in women with breast and gynecological cancers compared to those with hematologic malignancies. 46,47 Ovarian stimulation protocols take 10-14 days to complete and can be started at any time of the menstrual cycle.…”
mentioning
confidence: 99%